Search for genetic markers for selection and breeding aimed at increasing birth weight of piglets - E. A. Romanets; T. S. Romanets; O. L. Tretyakova; L. V. Getmantseva (Аграрная наука Евро-Северо-Востока, 2023)
With the intensive increase in the fertility traits of sows, the problem of decreasing the weight of piglets at birth has arisen. In this connection, the search for genetic variants associated with the birth weight of piglets is of particular relevance and scientific significance. The aim of the work was to identify genetic variants associated with piglet weight at birth and test them to select optimal genetic markers for selection and breeding work to improve reproductive performance of pigs on the basis of full genomic genotyping data using the Fst method. The studies were conducted in 2020-2022 on Large White pigs (n=239) bred at CJSC Plemzavod-Yubileiny in the Tyumen Region. Genotyping was performed using GeneSeek® GGP Porcine HD Genomic Profiler v1 (Illumina Inc., USA). Genomic data were filtered according to the following parameters --geno 0.1, -mind 0.1, -maf 0.05, -hwe 1e-7, --indep-pairwise 50 5 0.8. To identify genomic regions associated with piglet birth weight, there was used Fst statistics comparing genetic variants in pigs between two groups with high and low indices. Those in which the Fst values exceeded the quantile level of 0.999 were considered significant variants. Student's test was used to evaluate the significance of the effects of variant genotypes on the birth weight and number of piglets at birth. The results showed that there was a moderate negative relationship (-0.351) between piglet birth weight and number of piglets at birth. 17 SNPs associated with birth weight of piglets were identified, 9 of which were located in the KIF13A, STK24, FDFT1, ADGRD1, STX2, TMEM132D, ENSSSCG00000054866, ENSSSCG00000058459 genes, as well as SNPs rs81450496, rs80887103 in intergenic regions have been identified as promising genetic markers for increase in birth weight of piglets. The results obtained can be used to create domestic breeding technologies that improve the efficiency of pig breeding.